Trustworthiness in qualitative inquiry as a foundation for rigorous research - M Agung Akbar (Science Center Group, 2026)
Trustworthiness represents a fundamental criterion for ensuring rigor and scientific validity in qualitative research. Qualitative inquiry provides in-depth insights into human experiences within complex social and healthcare contexts; however, its credibility depends on systematic methodological rigor. This paper discusses the four core components of trustworthiness—credibility, dependability, confirmability, and transferability—as essential foundations for rigorous qualitative research. Credibility emphasizes accurate representation of participants’ lived experiences, dependability focuses on methodological consistency and transparency, confirmability ensures neutrality grounded in empirical evidence, and transferability addresses contextual applicability of findings. Various strategies, including prolonged engagement, triangulation, member checking, audit trails, reflexive journaling, and thick description, enhance trustworthiness across qualitative studies. Strengthening trustworthiness not only improves research quality but also increases confidence in qualitative findings for healthcare practice, policy development, and academic scholarship. Therefore, systematic application of trustworthiness principles is essential for producing reliable, meaningful, and impactful qualitative research outcomes.